Effect on quality of life of switching to combined oral contraception based on natural estrogen: an observational, multicentre, prospective phase IV study (ZOCAL Study). (3rd July 2016) - Lete, Iñaki; de la Viuda, Esther; Pérez-Campos, Ezequiel; Martínez, María Ángeles Gómez; Sanchez-de la Rosa, Rainel; Novalbos, Jesús; Sánchez-Borrego, Rafael
Abstract: Objectives: This observational, multicentre, prospective phase IV study examined change in health-related quality of life (QOL) from baseline to 6 months in women initiating combined oral contraception (COC) based on natural estrogen. Methods: Eligible women attending a baseline and 6-month gynaecology appointment belonged to one of three groups: group 1 used barrier contraception (condoms) and elected to continue this method; group 2 used condoms and elected to switch to COC based on natural estrogen; group 3 used COC based on ethinylestradiol and elected to switch to COC based on natural estrogen. The Spanish Society of Contraception (SEC)-QOL scale assessed health-related QOL. Secondary outcomes included symptoms of premenstrual syndrome, intermenstrual bleeding, duration and intensity of menstrual bleeding, contraception continuation rate, and tolerability. Results: A total of 857 women were enrolled and 785 completed the study. Group 2 ( n  = 224 completed) had significantly lower SEC-QOL global and dimension scores at baseline and significantly greater increases in SEC-QOL from baseline to 6 months compared with groups 1 ( n  = 72) and 3 ( n  = 489). Group 3 reported a similar SEC-QOL score to that of group 1 at baseline but showed significantly greater improvement in SEC-QOL global and psychological scores from baseline to 6 months. Among women receiving COC based on natural estrogen, the contraception continuation rate was 713/780 (91.4%); treatment-related adverse events were reported by 13/780 (1.7%). Conclusions: Improved SEC-QOL after 6 months was found in women who were dissatisfied with their current contraception at baseline and chose to switch to COC based on natural estrogen.